EXPLORING THE ART OF WORD COMBINATION CREATIVE WAYS TO CONSTRUCT SENTENCES (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This article explores the diverse landscape of sentence types and their significance in effective communication. Beginning with declarative sentences and moving through interrogative, imperative, exclamatory, conditional, and assertive sentences, the author emphasizes how each type serves a distinct purpose. By providing clear examples, the article aims to enhance the reader's ability to wield various sentence structures for impactful expression. Focusing on the intricacies of descriptive language, this article delves into the role of modifiers in enhancing written expression. It discusses the use of adjectives and adverbs to add depth to sentences, explores the power of similes and metaphors in creating vivid imagery, and emphasizes the importance of sensory language. The article aims to guide writers in employing descriptive language to engage readers and bring their narratives to life.